2017
DOI: 10.1377/hlthaff.2016.1185
|View full text |Cite
|
Sign up to set email alerts
|

Racial And Ethnic Differences In The Frequency Of Workplace Injuries And Prevalence Of Work-Related Disability

Abstract: Occupational injuries and illnesses lead to significant healthcare costs and productivity losses for millions of workers each year. This study tested for differences in the risk of workplace injuries and the prevalence of work-related disabilities for minorities compared to non-Hispanic white workers using national survey data. Non-Hispanic black workers and foreign-born Hispanic workers worked in jobs with the highest injury risk on average, even adjusting for education and gender. These elevated levels of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 48 publications
5
57
2
3
Order By: Relevance
“…This finding aligns with work by Gronlund and others that found people of color were more likely to suffer from HRI in the Unites States and that Latino workers bear a disproportionate burden of workplace injuries 18,43 . If we want to effectively address the health disparities present in WA, we must be able to guarantee the protection of vulnerable communities in their place of work.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding aligns with work by Gronlund and others that found people of color were more likely to suffer from HRI in the Unites States and that Latino workers bear a disproportionate burden of workplace injuries 18,43 . If we want to effectively address the health disparities present in WA, we must be able to guarantee the protection of vulnerable communities in their place of work.…”
Section: Discussionsupporting
confidence: 81%
“…As of 2016, only 12.1% of WA's workforce identifies as Latino, indicating that HRI is likely disproportionally affecting Latino workers in WA.32 Workers' compensation data likely provides an underestimation as previous research has found that Hispanic workers were less likely to file workers' compensation claim for nonfatal injuries due to fear of reprisal from their employer 42. This finding aligns with work by Gronlund and others that found people of color were more likely to suffer from HRI in the Unites States and that Latino workers bear a disproportionate burden of workplace injuries 18,43. If we want to effectively address the health disparities present in WA, we must be able to guarantee the protection of vulnerable communities in their place of work.Incorporating reliable and complete data on race and ethnicity into occupational safety and health data systems, for example, workers compensation and the BLS SOII, will allow the detection of racial and ethnic disparities in occupational injuries and illness.…”
supporting
confidence: 82%
“…The use of new technologies in decision-making must also be protected from perpetuating or amplifying existing health disparities. Extensive literature documents the disproportionate health and environmental hazards faced by many communities of color, low-income communities, and Indigenous communities (Bullard 2000;Burwell-Naney et al 2013;Lee and Mohai 2012;American Lung Association 2001;Davis et al 2016;Seabury et al 2017;Zota and Shamasunder 2017). Disproportionate exposures to toxic chemicals coupled with exposures to social hazards (e.g., poverty) can result in an amplification of harm faced by these communities (Gee and Payne-Sturges 2004).…”
Section: Values In Decision-makingmentioning
confidence: 99%
“…A study in the US analysed data from two national surveys asking respondents whether they had any health limitations affecting their work, and whether the condition was caused by injury. 6 Results showed that, compared with US-born Hispanic workers, overseas-born Hispanic workers had higher work-related injury rates but lower work-related disability. The authors noted that disabled workers among the overseas-born Hispanic migrants may have returned home, due to their inability to work.…”
mentioning
confidence: 95%
“…Few studies have investigated the burden of post‐injury disability among migrant populations. A study in the US analysed data from two national surveys asking respondents whether they had any health limitations affecting their work, and whether the condition was caused by injury 6 . Results showed that, compared with US‐born Hispanic workers, overseas‐born Hispanic workers had higher work‐related injury rates but lower work‐related disability.…”
mentioning
confidence: 99%